Penerapan Standar Akuntansi Keuangan Entitas Mikro,Kecil dan Menengah (SAK EMKM) dalam Penyusunan Laporan Keuangan pada UMKM di Kecamatan Indramayu - Margono, Bagus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the level of understanding, financial reporting practices, and the extent to which the Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) are implemented by MSME actors in Indramayu District. This research employs a descriptive qualitative approach using a case study method on selected MSMEs through purposive sampling. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using the Miles and Huberman interactive model. The results indicate that MSME actors’ understanding of SAK EMKM remains very low; most respondents had never heard of or understood the standard. In practice, financial reporting is still informal and simplistic, mostly limited to manual records without standardized structure. None of the observed MSMEs prepared complete financial statements based on SAK EMKM requirements. The main obstacles in implementing SAK EMKM include low accounting literacy, lack of technical assistance, and the perception that accounting is irrelevant for small-scale businesses. These findings highlight the urgent need for continuous outreach, technical training, and collaboration among local governments, educational institutions, and professional associations to enhance accounting literacy and support SAK EMKM adoption among MSMEs. Proper implementation of the standard is expected to promote transparency, professionalism, and easier access to financing for MSME actors in the future.